Pentingnya Menanamkan Nilai-Nilai Pancasila pada Siswa Kelas IV di Sekolah Dasar - Desclarista Salwa Putri; Vallen Syiah; Fadila Ramadhani; Ari Suriani; Afriza Media (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article aims to investigate the importance of instilling Pancasila values ​​in grade IV elementary school students as the main basis for children's moral development. This study was conducted using a literature review method through analysis of various articles from sources such as academic journals and Google Scholar, using the keywords